Simulasi Alat Photoplethysmograph (PPG) - Indra Jaya; Wisma Wisma (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
Heart is a vital organ in the human body. The heart functions circulated the blood throughout the body. The volume of blood in a body organ will vary due to blood pumping by the heart. Photoplethysmograph (PPG) is a device that can detect changes in blood volume using optical sensors. The purpose of this research is to make Photoplethysmograph monitoring system online. That is a device to monitor blood volume changes and display the change graph. Fluctuations in blood volume changes are influenced by the rhythm of blood pumping by the heart. Each peak on the PPG signal is correlated with one heartbeat. Photoplethysmograph charts can be used to determine the condition and abnormalities of a person's heart. Photoplethysmograph system online is realized in the form of sensors, amplifiers, LPF, ADC, and microcontroller as a serial interface, wiz610wi module, and web applications as online PPG graph viewer. Sensors composed of red LED and photoresistor (LDR) are placed on the fingers. The rays emitted by the LEDs are received by the LDR. The signals received by the LDR vary according to the volume of blood changes. The sensor output signal is then amplified and filtered. Incoming filter output signal ADC, serial interface by AT89C2051 then by wiz610wi module transmitted for display and monitored. Obtained Devices and apps created have worked well. The signal shown is pretty good, clean of noise. Transmission distance measured up to 70 m with delay less than 200 ms. The average heart rate calculation was in error 3%